2019
DOI: 10.26434/chemrxiv.8179244.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curating Metal-Organic Frameworks to Compose Robust Gas Sensor Arrays in Dilute Conditions

Abstract: Metal-organic frameworks (MOFs)-- tunable, nano-porous materials-- are alluring recognition elements for gas sensing. Mimicking human olfaction, an array of cross-sensitive, MOF-based sensors could enable analyte detection in complex, variable gas mixtures containing confounding gas species. Herein, we address the question: given a set of MOF candidates and their adsorption properties, how do we select the optimal subset to compose a sensor array that accurately and robustly predicts the gas composition via mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 90 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…Our approach for array design was borrowed from Sturluson et al, who showed that the array with the best sensitivity could be determined by performing a singular value decomposition on the matrix of Henry’s coefficients for each array, with the best array having the largest minimum singular value . In our work, we used CLACs rather than Henry’s coefficients, but otherwise this method is identical.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach for array design was borrowed from Sturluson et al, who showed that the array with the best sensitivity could be determined by performing a singular value decomposition on the matrix of Henry’s coefficients for each array, with the best array having the largest minimum singular value . In our work, we used CLACs rather than Henry’s coefficients, but otherwise this method is identical.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous works, we used computational methods to rapidly design gas-sensing arrays for the detection of methane and carbon dioxide, using metal–organic frameworks (MOFs) as the sensing elements. MOFs are high-surface-area porous crystals that have been widely explored for gas storage and separation and more recently have gained attention for gas-sensing applications. MOFs offer advantages for gas-sensing that stem from their structural and chemical diversity, tunability, and high internal surface areas, resulting in impressive gas adsorption with varied sensitivity. Furthermore, as crystalline materials, their gas adsorption properties can be predicted using well-established computational techniques. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of studies have investigated the use of metal-organic frameworks (MOFs) for improving electronic noses [16][17][18][19][20]. MOFs are promising materials for gas adsorption applications due to their nanoporous nature, high internal surface areas, and ease of tunability [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there has been little work on systematically finding the best combinations of MOFs for an array, and with thousands of MOFs to choose from, and thus well over 10 50 possible arrays, determining the top performing arrays is highly non-trivial. A recent paper by Sturluson et al made significant progress in this area by computationally designing MOF-based gas sensing arrays for the detection of CO2 and SO2 in dilute conditions [20]. In their paper, they calculated the Henry's coefficients for each gas/MOF to design an array of elements with maximal complementarity, and consequently the best signal.…”
Section: Introductionmentioning
confidence: 99%